Keterampilan Motorik Kasar Anak Usia Dini Ditinjau Dari Jenis Kelamin - Dinita Vita Apriloka (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2020)
Motor skills are physical through coordinated nerve, nerve and muscle center activities that are very important in early childhood growth and development, so training or familiarizing children with gross motor skills through creative play is a stage in supporting their growth and development. However, sometimes what happens when the gross motor skills of children are poorly trained. Therefore this study aims to determine current developments in children's gross motor skills that are reviewed by sex. The research method used was Pre-Experiment Design with One Group Pretest Posttest Design. This research was conducted in PAUD Khoerul Anwar with a population of 12 students in class A. Based on the results of the study and conducting research results showed that the gross motor skills of young children using creative games on boys and girls there were no differences.